2014
DOI: 10.3310/hta18270
|View full text |Cite|
|
Sign up to set email alerts
|

An assessment of the cost-effectiveness of magnetic resonance, including diffusion-weighted imaging, in patients with transient ischaemic attack and minor stroke: a systematic review, meta-analysis and economic evaluation

Abstract: BackgroundPatients with transient ischaemic attack (TIA) or minor stroke need rapid treatment of risk factors to prevent recurrent stroke. ABCD2 score or magnetic resonance diffusion-weighted brain imaging (MR DWI) may help assessment and treatment.ObjectivesIs MR with DWI cost-effective in stroke prevention compared with computed tomography (CT) brain scanning in all patients, in specific subgroups or as ‘one-stop’ brain-carotid imaging? What is the current UK availability of services for stroke prevention?Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 359 publications
(578 reference statements)
3
74
0
3
Order By: Relevance
“…The present study provides preliminary evidence that early exercise and education engagement could significantly reduce the economic burden associated with recurrent vascular events post-stroke/TIA [2]. This study has shown that the costs associated with hospital admissions were 141% higher in the usual care control group compared to those randomized to the exercise and education program.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…The present study provides preliminary evidence that early exercise and education engagement could significantly reduce the economic burden associated with recurrent vascular events post-stroke/TIA [2]. This study has shown that the costs associated with hospital admissions were 141% higher in the usual care control group compared to those randomized to the exercise and education program.…”
Section: Discussionmentioning
confidence: 55%
“…Stroke is the second most common cause of death, the primary cause of dependency, creates a huge societal burden and costs billions to the global economy in health and social care costs [1,2]. A transient ischemic attack (TIA) is an ischaemic brain attack with focal cerebral or retinal symptoms that last under 24 hours, usually less than 1 hour [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 This has sparked a shift towards use of a tissue-based definition of TIA. However, timely access to MRI and expert interpretation is not always available, and MRI is not cost-effective compared to CT. 20 It also remains to be seen whether use of plasminogen activator in patients with recent prior clinical symptoms lasting <24 hours associated with small MRI lesions is safe and effective. For these reasons, a tissue-based definition of TIA has yet to be widely endorsed.…”
Section: Discussionmentioning
confidence: 99%